Layered double hydroxides as PVC thermal stabilisers : the effect of particle size and concentration - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2016)
Dissertation (MEng)--University of Pretoria, 2016.